Subkultur pada Kehidupan Biker Chopper dalam Ilustrasi Digital Kartunal - Rofiq Syarifudin; Mujiyono Mujiyono (Universitas Sultan Ageng Tirtayasa, 2026)
The chopper biker subculture is often viewed negatively by society due to media stereotypes that emphasize its harsh and extreme aspects. In fact, this community possesses complex cultural and social values, such as freedom, brotherhood, and spirituality. Cartoony-style digital illustration becomes an effective medium for presenting another side of this subculture through symbols, colors, and communicative visual stylization. This creative research on digital illustration aims to explore cartoony-style chopper biker visuals combined with the values of freedom, spirituality, and solidarity. The creative process was carried out through the collection of visual references, sketching, clean line art, digital coloring, and finalization using Ibis Paint X. The results show that the stylization of forms, bold lines, and contrasting color palettes are able to strengthen visual character and convey deep philosophical meaning. The resulting illustrations not only present the aesthetics of the chopper subculture but also function as an effective medium of cultural communication in conveying social and spiritual narratives